2014
DOI: 10.7150/ijms.8428
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of Toll-like Receptor 8 and Its Relationship with VEGF and Bcl-2 in Cervical Cancer

Abstract: BACKGROUND: Cervical cancer is one of the most common cancers in women worldwide, often associated with the infection of human papillomavirus (HPV). Toll-like receptor 8 (TLR8), a pattern recognition receptor, is involved in viral nucleic acid sensing. Recently TLR8 has been shown to be expressed in cancer cells, and it has been suggested that it may help cancer cell growth and tumor development. The objective of this study is to investigate the expression of TLR8 expression and its relationship with Bcl-2 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 23 publications
0
27
0
2
Order By: Relevance
“…Bcl-2 promotes the proliferation of cancer cells (16,17). In addition, Bcl-2 is overexpressed in cervical cancer cells and is closely correlated with the development and progression of cervical cancer (18). Bax belongs to the Bcl-2 family and forms dimers with Bcl-2 to regulate the balance between cell proliferation and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Bcl-2 promotes the proliferation of cancer cells (16,17). In addition, Bcl-2 is overexpressed in cervical cancer cells and is closely correlated with the development and progression of cervical cancer (18). Bax belongs to the Bcl-2 family and forms dimers with Bcl-2 to regulate the balance between cell proliferation and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…These molecules activate specific TLRs, leading to further chronic inflammation, which is one of the main cancer-promoting factors (28). The expression of TLRs in the tumor microenviroment directly influences tumor development and its interactions with the immune system (38). The activation of TLRs upregulates pro-oncogenic pathways via the induction of nitric oxide synthase and cyclooxygenase 2, which regulate the expression of TLRs and promote a positive feedback mechanism, thus leading to the progression of cancer and the development of more aggressive neoplastic phenotypes (38).…”
Section: Resultsmentioning
confidence: 99%
“…TLRs are also capable of recognizing molecular patterns that are typical of endogenous cellular damage (DAMPs), and are thus implicated in processes of cellular proliferation and survival, apoptosis, angiogenesis and tissue remodelling (36). TLRs are expressed by immune cells and other cellular types, including cancer cells (37,38). Significant quantities of DAMPs are released in the tumor microenviroment by damaged epithelial cells and necrotic tumor cells (28).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to TLR9, the TLR3/5/8 pathways are activated in hrHPV-infected KCs. High expression levels of TLR8 in cervical cancer cells are associated with the upregulated expression of B-cell lymphoma-2 and vascular endothelial growth factor in these cells (27). A previous study found that there is marked TLR4 expression in hrHPV-positive cells and that its expression is associated with the virus type, as well as the histopathological grade.…”
Section: Hpv Infection Regulating the Host Immune Responsementioning
confidence: 99%